The impact of complexity management on dynamic capabilities: a survey at some private colleges - zahim, Muthana; gwad, Nadhum (Journal of Economics and Administrative Sciences, 2021)
This research aims to understand complexity management and its impact on the use of the dynamic capabilities of a sample of private colleges.  Private colleges are currently facing many crises, changes, unrest and high competitive pressures.  Which is sometimes difficult or even impossible to predict.  The recruitment of dynamic capabilities is also one of the challenges facing senior management at private colleges to help them survive and survive.  Thus, the problem of research was (there is a clear insufficiency of interest in Complexity Management and trying to employ it in improving the dynamic capabilities of Colleges that have been discussed?). A group of private colleges was selected as a field of application, as the sample of the research was selected in a simple random sample method of Senior leadership of private colleges, and the sample size was (143) persons, The questionnaire was adopted as a tool for obtaining research data, which was prepared on the basis of a number of ready-made measurements, The statistical tools produced a number of results, most of which confirmed the existence of a morally significant effect of managing complexity in its dimensions (interdependence, and diversity management, and uncertainty) in the employment of the dynamic capabilities of private colleges, and therefore the main hypothesis contained in the research was accepted